Pengaruh Konsumsi Nugget Ikan Teri Terhadap Peningkatan Kadar Haemoglobin Pada Remaja Putri di SMAN 1 Binamu, Jeneponto - Syahridayanti, Syahridayanti; Nurmitasari, Nurmitasari; Afni, Nur; Elmika, Elma (Fakultas Perikanan UCM, 2024)
Anemia characterized by fatigue, weakness, and exhaustion, which may hinder creativity and productivity. Adolescent girls are particularly vulnerable to this condition due to their increased requirements for iron and protein during periods of rapid growth. This study aimed to examine the effectiveness of anchovy nugget consumption in raising hemoglobin levels among female students at SMAN 1 Binamu, Jeneponto. Utilizing a quantitative quasi-experimental design with a nonequivalent control group, a total of 60 eleventh-grade students were selected through purposive sampling—30 were assigned to receive anchovy nuggets as an intervention, while the remaining 30 were given iron tablets (Fe). Hemoglobin levels were measured both before and after the intervention. Data were analyzed using the Wilcoxon and Mann–Whitney tests. The results revealed a significant increase in hemoglobin levels in the anchovy nugget group (p = 0.001; p < 0.05), indicating that this intervention was effective in improving hemoglobin levels among adolescent girls at SMAN 1 Binamu.